Potential of ultrasound stimulation and sonogenetics in vision restoration: a narrative review - Jie Ji; Chen Gong; Gengxi Lu; Junhang Zhang; Baoqiang Liu; Xunan Liu; Junhao Lin; Patrick Wang; Biju B. Thomas; Mark S. Humayun; Qifa Zhou (Neural Regeneration Research)
Vision restoration presents a considerable challenge in the realm of regenerative medicine, while recent progress in ultrasound stimulation has displayed potential as a non-invasive therapeutic approach. This narrative review offers a comprehensive overview of current research on ultrasound-stimulated neuromodulation, emphasizing its potential as a treatment modality for various nerve injuries. By examining of the efficacy of different types of ultrasound stimulation in modulating peripheral and optic nerves, we can delve into their underlying molecular mechanisms. Furthermore, the review underscores the potential of sonogenetics in vision restoration, which involves leveraging pharmacological and genetic manipulations to inhibit or enhance the expression of related mechanosensitive channels, thereby modulating the strength of the ultrasound response. We also address how methods such as viral transcription can be utilized to render specific neurons or organs highly responsive to ultrasound, leading to significantly improved therapeutic outcomes.